2018
DOI: 10.1007/s10661-017-6419-z
|View full text |Cite
|
Sign up to set email alerts
|

Multiple linear regression and regression with time series error models in forecasting PM10 concentrations in Peninsular Malaysia

Abstract: Frequent haze occurrences in Malaysia have made the management of PM (particulate matter with aerodynamic less than 10 μm) pollution a critical task. This requires knowledge on factors associating with PM variation and good forecast of PM concentrations. Hence, this paper demonstrates the prediction of 1-day-ahead daily average PM concentrations based on predictor variables including meteorological parameters and gaseous pollutants. Three different models were built. They were multiple linear regression (MLR) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(20 citation statements)
references
References 11 publications
1
19
0
Order By: Relevance
“…Table 1 summarizes several AI techniques in predicting PM 10 concentration and TSP. Also, similar and relevant work on the prediction of PM 10 concentration can be found at the following references [52][53][54][55][56][57][58][59][60][61]. Given the previous work, it can be seen that it is feasible to use AI techniques to predict dust concentration as well as PM 10 emissions.…”
Section: Introductionmentioning
confidence: 86%
“…Table 1 summarizes several AI techniques in predicting PM 10 concentration and TSP. Also, similar and relevant work on the prediction of PM 10 concentration can be found at the following references [52][53][54][55][56][57][58][59][60][61]. Given the previous work, it can be seen that it is feasible to use AI techniques to predict dust concentration as well as PM 10 emissions.…”
Section: Introductionmentioning
confidence: 86%
“…In this study multiple linear regression (MLR) (İçağa and Sabah 2009;Ng and Awang 2018;Sousa et al 2007;Ul-Saufie et al 2012) was used to determine the relationship between daily COVID-19 confirmed cases density (CCD) and the average concentrations of the four criteria air pollutants (i.e., CO, NO 2 , O 3 , and SO 2 ). CCD is obtained by dividing the number of total confirmed cases by the population size.…”
Section: Multiple Linear Regressionmentioning
confidence: 99%
“…For example, if R 2 = 0.80, it means that 80% points will be included inside the regression track. A higher value of R 2 indicates a better fit for the given dataset [22]. It also helps to examine how differences in one parameter can be explained by a difference in a second variable.…”
Section: Developing Statistical Model For the Process Performance Chamentioning
confidence: 99%